Edukasi Gizi Seimbang Untuk Mencegah Malnutrisi Pada Anak - Nining Tunggal Sri Sunarti; Retno Heru Setyorini; Fitriani Mediastuti (Jurnal Kemitraan Masyarakat, 2024)
The growth and development of toddlers are crucial in determining the welfare of a nation, as this period serves as the foundation for a healthy and productive future generation. Nutritional deficiencies in the early years of life can lead to stunting, which not only hinders a child's physical growth but also negatively impacts their learning abilities and immune system in the future. Addressing nutritional issues is essential by increasing mothers' knowledge. This activity aims to evaluate the effectiveness of nutrition education on balanced nutrition in preventing malnutrition in children at Posyandu Ngireng-ngireng, Kalurahan Panggungharjo. The education program was conducted using a lecture and Q&A method, supported by PowerPoint presentations displayed via LCD. The pre-test and post-test results showed a significant increase in participants' knowledge, with the average score rising from 54.38 to 71.56. These results indicate that the lecture method, supported by visual media and interactive Q&A sessions, effectively enhances mothers' understanding of the importance of balanced nutrition. Therefore, this approach can be adopted in other health education programs to improve community knowledge about nutrition and child health